INTEGRATING TRADITIONAL ECOLOGICAL KNOWLEDGE IN TELUK BINTUNI DISTRICT: OPPORTUNITIES AND CHALLENGES FOR SUSTAINABLE RESOURCE MANAGEMENT - Nimrod Agustinus Andyratnah Rumayomi; Agustinus Murdjoko; Antoni Ungirwalu; Mulyadi Mulyadi; Nithanel Mikael Hendrik Benu; Dony Aristone Djitmau (BIOTROPIA, 2025)
HIGHLIGHTS- Traditional knowledge plays a crucial role biodiversity conservation. - In Teluk Bintuni District, local regulations support the integration of traditional knowledge, promoting collaboration for sustainable resource management. - The study highlights the need for community engagement, capacity building, and education to effectively utilize traditional ecological.- Successful conservation initiatives require collaboration to balance economic growth with environmental stewardship and social inclusivity, ultimately fostering sustainable development. ABSTRACTTraditional knowledge is vital for wildlife management and forest conservation in tropical regions and is passed down through generations.  Thus, this research was designed to identify the challenges and opportunities encountered in implementing Traditional Ecological Knowledge (TEK) during regional development, particularly in relation to natural resource management in Teluk Bintuni District.  The data were collected through interviews with local people and a Focus Group Discussion (FGD) involving government officials, Non-Governmental Organizations (NGOs), and local figures.  The results revealed that the government had enacted Regional Regulation Number 1 of 2019 to recognize the customary rights of seven tribes, i.e., the Kuri, Wamesa, Irorutu, Sebyar, Simuri, Sougb, and Moskona tribes, thereby protecting traditional communities.  The regulations emphasize the prioritization of people's rights in development, supported by the establishment of LMA Tujuh Suku (a Traditional Community Institution of Seven Tribes).  The tribes have been utilizing TEK to deal with social and environmental issues, integrating the issues into development procedures to foster conservation and economic growth.  The challenges, such as poor infrastructure, political instability, and low community engagement, hinder effective implementation.  The strengths include accessible natural resources and international funding for conservation.  The study highlighted the importance of education, stakeholder collaboration, and technology in documenting and incorporating TEK into conservation planning through participatory research, capacity building, and adaptive management.